Operations Management in Automotive Industries From Industrial Strategies to Production Resources Management, Through the Industrialization Process and Supply Chain to Pursue Value Creation - Gobetto, Marco; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This book has proved its worth over the years as a text for courses in Production Management at the Faculty of Automotive Engineering in Turin, Italy, but deserves a wider audience as it presents a compendium of basics on Industrial Management, since it covers all major topics required. It treats all subjects from product development and (3z(Bmake or buy(3y(B-decision strategies to the manufacturing systems setting and management through analysis of the main resources needed in production and finally exploring the supply chain management and the procurement techniques. The very last chapter recapitulates the previous ones by analysing key management indicators to pursue the value creation that is the real purpose of every industrial enterprise. As an appendix, a specific chapter is dedicated to the basics of production management where all main relevant definitions, techniques and criteria are treated, including some numerical examples, in order to provide an adequate foundation for understanding the other chapters. This book will be of use not only to Automotive Engineering students but a wide range of readers who wish to gain insight in the world of automotive engineering and the automotive industry in general.s
Foreword -- About the author -- Introduction -- Acknowledgements -- 1 Historical Outlines and Industrial Strategies for Automotive Industries -- 1.1 Historical Outlines in Automotive Industries -- 1.2 Strategic Planning of Production Activities -- 1.3 Process Integration and (3z(BMake or Buy(3y (BDecision Making -- 1.4 Manufacturing Systems$1 (BSet-Up and Location Criteria -- 1.5 Technologies for Materials Applied to Vehicles$1 (BConstruction Overview -- 1.6 Sketches for Manufacturing Systems Adopted in Cars Manufacturing -- 1.7 Systems$1 (BStrategical Prerogatives -- 2 From project to product -- 2.1 Standardization Logics and Project Setting Up -- 2.2 Industrialization Process Description -- 2.3 Product/Process Information Technology System -- 2.4 Product Composition Analysis -- 2.5 Product Technical Changes Management -- 3 Manufacturing Engineering and Equipment Efficiency Evaluation -- 3.1 Manufacturing Engineering Planning and Executive Project -- 3.2 Production Capacity Setting -- 3.3 Working Time Analysis Methodologies -- 3.4 Man/Machine Interaction and Standard Working Time Defining -- 3.5 Equipment Times Deployment Diagram -- 3.6 Integrated Production System Introduction -- 3.7 Operative Productivity and Flexibility -- 3.8 Equipment and Machine Loading -- 3.9 Installed Productive Capacity Defining -- 4 Work Analysis and Labour Productivity Evaluation Criteria -- 4.1 Activity Level and Labour Efficiency -- 4.2 Manpower Planning -- 4.3 Working Time Length and Flexibility -- 4.4 Labour Productivity and Improvement Plans -- 4.5 Input Data for Operative Control -- 4.6 Tasks Assignment and Workload Balancing -- 4.7 Production Employees Motivation and Rewarding -- 5 Manufacturing System Management and Maintenance Criteria -- 5.1 Plant Manufacturing System -- 5.2 Equipment Reliability and Maintainability -- 5.3 Maintenance Management -- 5.4 Costs and Maintenance Effectiveness Correlation -- 5.5 General and Complementary Equipment for Production -- 5.6 Tools and Consumables Management -- 5.7 (3z(BTotal Productive Maintenance(3y (Bapproach -- 6 Logistics and Supply Chain Basics for Automotive Application -- 6.1 Logistics Historical Evolution and Actual Strategies -- 6.2 Logistics Flows in the Supply Chain -- 6.3 Material Handling and Inventory Management Methodologies -- 6.4 Production and Delivery Planning -- 6.5 Logistics Information Technology Systems -- 6.6 Logistics Key Performance Indicators -- 7 Global Purchasing Operations -- 7.1 Purchasing Department$1 (Bs Role -- 7.2 Purchasing Policies Evolution -- 7.3 Purchasing Marketing and Global Sourcing Policies -- 7.4 Suppliers Network Management -- 7.5 Order Procedure and Cooperation Agreements -- 7.6 Supplying Cost and Purchasing Effectiveness Indicators -- 7.7. (3z(BE-Procurement(3y (BTechniques -- 8 Quality Management and Continuous Improvement -- 8.1 The (3z(BLearning Curve(3y (BConcept -- 8.2 Production Ramp Up and Maximum Rate Achievement -- 8.3 Quality Management in Industrial Processes -- 8.4 Quality and Reliability Assurance Techniques in Product Design Phase -- 8.5 (3z(BTotal Quality Management(3y (Band Continuous Improvement Approach -- 9 Value Creation and Final Considerations -- 10 (APPENDIX) Production Management Basics -- 10.1 The Product -- 10.2 Production Systems -- 10.3 Criteria for the Stock and Lots Management -- 10.4 Problems Connected to the Planning Horizon -- 10.5 APP (Aggregated Production Planning) -- 10.6 MPS (Master Production Schedule) -- 10.7 MRP (Material Requirement Planning) -- List of Abbreviations.s
Keywords: Engineering; Machinery; Engineering; Automotive Engineering; Manufacturing, Machines, Tools; Production/Logistics/Supply Chain Management